Application and analysis of the arthroscopic remnant-preserving technique to rotator cuff tear: a retrospective study - Bao, Tao; Yang, Yuxia; Hu, Yangyang; Fei, Wenyong (Frontiers in Surgery, 2025)
BackgroundFew studies have investigated the effect of remnant tissue in the footprint area on rotator cuff repair. This study aimed to compare the clinical and structural outcomes of remnant-preservation and remnant-removal techniques during arthroscopic rotator cuff repair.MethodsThis study compared arthroscopic remnant-preservation (RP) and remnant-removal (RR) techniques for rotator cuff repair in 68 patients (2–5 cm tears) with footprint remnant tissue. Patients were divided into the RP group (n = 33) and the RR (n = 35) group. Outcomes were assessed preoperatively and at 3, 6, and 24 months postoperatively. Evaluations included visual analog scale (VAS) pain scores, American Shoulder and Elbow Surgeons (ASES) and Constant–Murley (CS) scores, shoulder mobility, and MRI-based healing (Sugaya grade).ResultsAt 3 months, the RP group reported lower VAS scores than those in the RR group (1.4 ± 0.6 vs. 1.8 ± 0.7, P = 0.017). Shoulder forward flexion and abduction improved significantly in the RP group at 6 months (flexion, 159.5 ± 1.7° vs. 151.2 ± 1.7°; abduction, 145.1 ± 10.9° vs. 137.2 ± 11.1°, P ≤ 0.005) and 24 months (flexion, 167.2 ± 1.9° vs. 161.1 ± 1.8°; abduction, 161.2 ± 8.4° vs. 153.2 ± 13.9°, P ≤ 0.025). ASES scores were higher in the RP group at 6 months (95.0 ± 4.8 vs. 91.4 ± 6.8, P = 0.014) and 24 months (94.9 ± 3.8 vs. 89.4 ± 6.9, P = 0.001). MRI at 24 months demonstrated superior rotator cuff healing in the RP group (P = 0.008).ConclusionsThe remnant-preservation technique was associated with reduced early postoperative pain, better functional recovery in shoulder mobility, and enhanced rotator cuff healing compared with remnant removal. These findings suggest that preserving footprint remnant tissue during arthroscopic repair may optimize clinical and structural outcomes.